The Impact of Covid-19 on Economic Activity: Evidence from Administrative Tax Registers - Nikolay Angelov; Daniel Waldenström (Center for Economic Studies and ifo Institute (CESifo), 2021)
We use population-wide tax register data to document the impact of the COVID-19 pandemic on firm sales, tax revenues, and sick pay in Sweden. The pandemic impact is identified using within-year, between-year, and geographical variation, and our data allows us to run placebo tests. Our findings confirm the large negative effects of the pandemic, but shed new light on their magnitudes and sensitivity to COVID-19 morbidity rates. Specifically, we find that the impact on VAT and firm sales was larger than on commonly used industrial and service production indexes, larger than the effect on electricity for industrial use, but less than the effect on excise taxes on air travel. The pandemic's impact on short-term sick pay is large, but unlike tax payments, it does not vary with local infection rates, indicating behavioral responses to more generous rules for sickness insurance during the pandemic.
Keywords: H24; H25; J22; J24; 330; Covid-19 impact; VAT; excise taxes; sick pay